INDONESIA’S FOREIGN POLICY DURING SOEKARNO ERA 1945 – 1965 - Indrayani, Irma; Umar, Harun; Mellaz, August (Universitas Nasional, 2020)
This paper aims to see the shift of Indonesia’s foreign policy from diplomacy to a confrontation during the Soekarno era from 1945 to 1965. The change of foreign policy orientation become a spotlight on this paper that explores the issue based on historical chronology, national interest, and the dynamics of international politic that shaped the goal of Indonesia’s international politics, that is to defend its independence and gaining recognition as an independent and sovereign country. The analysis used to study this shift of foreign policy of Indonesia, from diplomacy to confrontation is described using the qualitative method through a historical approach. The data and information used for analysis in this study are sourced from secondary data obtained from the literature study.